TEORI BELAJAR KOGNITIVISTIK DAN IMPLIKASINYA DALAM PROSES PEMBELAJARAN DI SEKOLAH DASAR - Pahru, Syaipul; Gazali, Munawir; Pransisca, Made Ayu; Marzuki, Ahmad Dedi; Nurpitasari, Nopi (LPPM Institut Pendidikan Nusantara Global, 2023)
Learning theory will make it easier for educators to carry out the form of learning that will be carried out. This article will review the theory of cognitive learning and will provide a complete understanding and explanation so that it can be applied in learning activities. This research is a literature study research, where in this research the writer tries to collect data related to the theory put forward by Ausubel and Gagne and then analyzes how the theory of the two figures is applied in learning in elementary schools. The results of this study are the first cognitive theory developed by Ausubel in his theory which states that cognitive processes are advanced organizers (initial arrangements), progressive differentiation, reconciliation reconciliation (integrative reconciliation), consolidation. Meanwhile, Gagne said that cognitive processes are through receptors, sensory registers, short-term memory, long-term memory, and response generators. In the learning process in elementary schools, cognitive theory is more directed and adapted to the age of students.